H11 Clinical Features of Depression in Huntington's Disease – A Cross Sectional Study Comparing Depressed Patients with and without HD. (17th September 2014) - Scaria, J; Rogers, D; Jones, M; Daly, C; Craufurd, D
Abstract : Background: Huntington's disease (HD) is characterised by a triad of motor, cognitive and psychiatric symptoms. Depression is common, but experience suggests that the clinical features of depression in patients with HD may differ from those in the general population, depression in HD being more variable from day to day, and more susceptible to changes in environmental factors and mental stimulation. Aim: To compare the clinical features of depression in Huntington's disease with depression in the general population. Methods: The subjects were 15 HD patients with depression and 15 depressed patients from an out-patient psychiatry clinic. Recruitment was based on inclusion criteria designed to select patients with moderate depression. The non-HD comparison group was matched for age, sex and Visual Analogue Mood Scores. Both groups completed the Hospital Anxiety and Depression Scale (HADS), Beck Depression Inventory, Test for Anhedonia questionnaire and a modified version of the Montgomery Asberg Depression Rating Scale with 3 questions added about environmental susceptibility of low mood. Results: There was no significant difference in the total score of all the questionnaires used. The anhedonia ('lack of enjoyment') item of the HADS was significantly lower in depressed patients with HD, but we did not find a similar difference for anhedonia items in other scales. Concentration difficulties and susceptibility of mood to environmental stimulation were greater in HD patients, but this difference did not attain statistical significance. Conclusion: The clinical features of depression in patients with HD were similar to those from the general population. However, this pilot study was statistically under-powered, and there was a clear trend for the depressed HD patients to report more improvement in mood with favourable environmental changes. We plan a further study to replicate this in a larger sample and to explore the temporal pervasiveness of low mood in the two groups.